1995
DOI: 10.1016/s0022-5223(95)70185-0
|View full text |Cite
|
Sign up to set email alerts
|

Tricuspid valve replacement: Fifteen years of experience with mechanical prostheses and bioprostheses

Abstract: Tricuspid valve replacement is not a common operation. The purpose of this study was to examine the early and late results in 60 patients who underwent 28 (47%) bioprosthetic and 32 (53%) mechanical tricuspid valve replacements. All operations took place between January 1978 and June 1993 during which period a total of 4741 patients underwent valve replacement operation. Mean patient age was 50 +/- 15 (18 to 75) years. Forty-one patients (68%) were female and 19 patients (32%) were male. Forty-nine patients (8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
47
1
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(55 citation statements)
references
References 28 publications
4
47
1
3
Order By: Relevance
“…This result is comparable with previous reports [6,7,12]. The most common cause of early death in this series was persistent underlying heart failure (54.5% of operative deaths).…”
Section: Commentsupporting
confidence: 92%
See 1 more Smart Citation
“…This result is comparable with previous reports [6,7,12]. The most common cause of early death in this series was persistent underlying heart failure (54.5% of operative deaths).…”
Section: Commentsupporting
confidence: 92%
“…The late mortality of 11.4% is comparable with or lower than other reports, which range from 9.2% to 57% [2, 7, 12, 16]. Some authors reported that there was no late mortality during their follow-up period [5,12]. In these 13 patients, nine underwent two or more valve operations.…”
Section: Commentsupporting
confidence: 75%
“…However, implantation of a prosthetic TV is associated with high risk of periprocedural death (7-40%) and high (30-50%) 10-year mortality. Leaving the lead in situ predisposes to LDTD recurrence, and positioning the lead in the cleft between prosthetic sutures makes it impossible to perform any percutaneous intervention in case of future problems with the lead or development of infection [18][19][20]. In the present study 1 patient necessitated implantation of a prosthetic TV; during the operation the pacing system was explanted and replaced for the epicardial one.…”
mentioning
confidence: 75%
“…16 Reported complications are complete heart block (6%), thromboembolism and thrombosis (1% per patient per year). 15 Survival after tricuspid valve replacement at 10 years' follow-up is 55%.…”
Section: Tricuspid Diseasementioning
confidence: 99%
“…15 Survival after tricuspid valve replacement at 10 years' follow-up is 55%. 16 Mortality is related to right ventricular dysfunction, dysrhythmias, endocarditis, other valve disease, stenosis or malfunction of implanted devices. 17 …”
Section: Tricuspid Diseasementioning
confidence: 99%